The phosphorescence and excitation-wavelength dependent fluorescence kinetics of large-scale graphene oxide nanosheets. Issue 37 (25th April 2017) - Zhao, Litao; Yu, Xiantong; Zhang, Sanjun; He, Xiaoxiao; Li, Lei; Jia, Menghui; Chang, Mengfang; Pan, Haifeng; Chen, Jinquan; Wang, Wenjun; Xu, Jianhua
Abstract : In this study, phosphorescence emission and a strong excitation-wavelength dependent fluorescence has been found in large-scale graphene oxide (GO) nanosheets. Abstract : In this study, phosphorescence emission and a strong excitation-wavelength dependent fluorescence has been found in large-scale graphene oxide (GO) nanosheets. GO was covalently functionalized with triphenylamine (GO-CONH-TPA) in order to enhance the GO fluorescence quantum yield to 18%. The intersystem crossing (ISC) dynamics were studied using a femtosecond transient absorption technique, which appeared in the same timescale as the fluorescence dynamics of GO-CONH-TPA in both a polar solvent and solid film. Therefore, both, the solvation (several hundreds of picoseconds) and the intersystem crossing (ISC) gave rise to the strong excitation-wavelength dependent fluorescence. Moreover, the phosphorescence emission of the GO-CONH-TPA film at room temperature has been described for the first time in this report, and the lifetime of phosphorescence was found to be 6.95 μs. The fluorescence kinetics of GO-CONH-TPA were attributed to the aromatic hydrocarbon-carboxylic domain structure of GO.